2011
DOI: 10.3399/bjgp11x583227
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identifying diabetes in optometric practice: a prospective study

Abstract: BackgroundUnconventional settings, outside general medical practice, are an underutilised resource in the attempt to identify the large numbers of people with undiagnosed diabetes worldwide. AimThe study investigated the feasibility of using optometry practices (opticians) as a setting for a diabetes screening service. Design and settingAdults attending high street optometry practices in northern England who selfreported at least one risk factor for diabetes were offered a random capillary blood glucose (rCBG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…None of these risk factors require the participants to have previously attended a GP. Though people may misreport their weight and height [20,21], resulting in underreporting of obesity levels, over 40% of participants in our study reported that they had a BMI of 25kg/m 2 or more, suggesting that people are willing to report this as a risk factor [11]. Only screening those aged 40 years or more with either a family history of diabetes or self reported BMI of 25kg/m 2 or more would have halved the number of tests carried out, and identified around two thirds of those who were diagnosed with hyperglycaemia following participation in the study.…”
Section: Cost Of Different Screening Strategiesmentioning
confidence: 91%
See 4 more Smart Citations
“…None of these risk factors require the participants to have previously attended a GP. Though people may misreport their weight and height [20,21], resulting in underreporting of obesity levels, over 40% of participants in our study reported that they had a BMI of 25kg/m 2 or more, suggesting that people are willing to report this as a risk factor [11]. Only screening those aged 40 years or more with either a family history of diabetes or self reported BMI of 25kg/m 2 or more would have halved the number of tests carried out, and identified around two thirds of those who were diagnosed with hyperglycaemia following participation in the study.…”
Section: Cost Of Different Screening Strategiesmentioning
confidence: 91%
“…14 Logistic regression showed the BMI of 25kg/m 2 or more, family history of diabetes and increased age increased the likelihood of having a rCBG of 6.1mmol/l or more [11]. None of these risk factors require the participants to have previously attended a GP.…”
Section: Cost Of Different Screening Strategiesmentioning
confidence: 99%
See 3 more Smart Citations